Biosorption of lead (II) from aqueous solution using Cellulose-based Bio-adsorbents prepared from unripe papaya (Carica papaya) peel waste: Removal Efficiency, Thermodynamics, kinetics and isotherm analysis - Wilavan Jaihan; Vanee Mohdee; Sompop Sanongraj; Ura Pancharoen; Kasidit Nootong (Arabian Journal of Chemistry, 2022)
This work focuses on the removal of lead from contaminated aqueous solutions using unripe papaya peel based bio-adsorbents (PP). Response surface methodology (RSM) based on Box-Behnken design (BBD) is employed to determine the independent variables. Optimum conditions proved to be 96.5 mg/L of initial lead concentration in solution, at pH 4 of aqueous solution, having adsorbent dosage of 14.6 g/L and contact time (3 h) which subsequently yielded the predicted and actual lead removal efficiencies of 100% and 97.54%, respectively. Adsorption isotherms and kinetics of lead adsorption using unripe papaya peel followed the Freundlich and pseudo-second-order models, indicating that the process of chemisorption occurred. The magnitude of the adsorption capacity of the pseudo-second-order model (qe,cal = 6.25 mg/g) was found to be comparable to the value obtained experimentally (qe,cal = 6.45 mg/g). Thermodynamic parameters were calculated in order to identify the phenomena of adsorption. The values of ΔH° and ΔS° are found to be 13.61 J/mol and 54.30 J/mol⋅K, respectively. The characteristics of unripe papaya peel bio-adsorbents, analyzed via SEM/EDX, FTIR and BET, are also presented. Thus, the O-H and C-O functional groups contained in the unripe papaya peel waste were found to effectively adsorb lead from the aqueous medium. The average pore diameters, average pore volumes and average surface area of bio-adsorbents prepared from unripe papaya peel waste proved to be 9.046 nm, 0.0012 cm3/g and 0.755 m2/g, respectively.